1998
DOI: 10.1002/hep.510270625
|View full text |Cite
|
Sign up to set email alerts
|

Delayed fas-mediated hepatocyte apoptosis during liver regeneration in mice: hepatoprotective role of TNFα

Abstract: Fas-mediated apoptosis is one of the major death processes of hepatocytes in liver diseases. Although compensatory regeneration occurs during liver injury, it has not been determined whether regenerating hepatocytes die by the same apoptotic process as quiescent hepatocytes. To clarify this issue, the hepatocyte apoptotic process, after injection of agonistic anti-mouse Fas, was compared between shamoperated mice and two-thirds partially hepatectomized mice. The onset of hepatocyte apoptosis was retarded in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 41 publications
3
34
0
Order By: Relevance
“…41 The milder liver involvement we observed in patients with TNF-␣ polymorphism, which was associated with an increased expression of TNF-␣ in most previous studies, [11][12] may reflect the hepatoprotective activity of this cytokine. 42 Alternatively, the reduction in liver necrosis may have been due to a lower accumulation of iron in hepatocytes, perhaps in favor of Kupffer cells and macrophages, although we have no clear evidence indicating that patients with TNF-␣ polymorphism had more severe siderosis in this cellular compartment.…”
Section: Discussionmentioning
confidence: 73%
“…41 The milder liver involvement we observed in patients with TNF-␣ polymorphism, which was associated with an increased expression of TNF-␣ in most previous studies, [11][12] may reflect the hepatoprotective activity of this cytokine. 42 Alternatively, the reduction in liver necrosis may have been due to a lower accumulation of iron in hepatocytes, perhaps in favor of Kupffer cells and macrophages, although we have no clear evidence indicating that patients with TNF-␣ polymorphism had more severe siderosis in this cellular compartment.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have shown that the regenerating liver is highly resistant to Fas-induced apoptosis. 30,31 To determine whether increased proliferation could account for the increased cell death resistance, 2 mutants on NTBC and 2 mutants off NTBC were given 2 doses of Bromodeoxyuridine (BrDU) i.p. either 2 and 14 hours before harvest or continuously for 7 days before sacrifice.…”
Section: Resultsmentioning
confidence: 99%
“…21,46,47 Protection against aFas-mediated toxicity has also been observed in the regenerating liver. Indeed, mice at 24 h after two-thirds hepatectomy are resistant to aFas-induced toxicity, 1,19 although the hepatocyte surface expression of Fas is unchanged. 19 On the other hand, sublethal doses of aFas afford protection against a subsequent lethal challenge with the same antibody, an effect that has been ascribed to the compensatory proliferation elicited by the first injection.…”
Section: Discussionmentioning
confidence: 99%
“…A sound body of evidence substantiates the notion that TNFa can trigger hepatocyte proliferation in vitro 16,17 as well as in vivo (reviewed by Michalopoulos and DeFrances 18 ), and that normal hepatocytes are inherently resistant to TNFa toxicity. Thus, TNFa promotes regenerative liver growth, subsequent to partial hepatectomy 19 or liver injury 20 , and growth elicited by agents such as gadolinium chloride 21 or peroxisome proliferators. 16 On the other side of the coin, TNFa has been involved in the induction of cell death in experimental hepatitis 22,23 and various liver diseases.…”
Section: Introductionmentioning
confidence: 99%